HAK ASUH ANAK PUBERITAS PASCA PERCERAIAN - Syazali, Hasan (Jurnal Tahqiqa : Jurnal Pemikiran Hukum Islam, 2023)
This paper discusses the issue of post-divorce puberty child custody. In our daily life we often encounter in society, that after the divorce of parents of children we often find that we lose our identity. We encounter various kinds of judgments in the midst of society towards divorced families. Even though the problem of divorce is not a new problem in Islam. Shari'a has arranged in such a way for every follower of Islamic teachings in a very systematic way. As we will discuss here, every husband and wife who has divorced Islam provides steps that are mutually beneficial, even children are also regulated by Shari'ah regarding the rights of children when their parents are separated. Therefore, parents should hold each other back to avoid divorce in the household for the sake of children who still need perfect attention and affection from both parents. According to Islam, the child has the right to be cared for by the mother if he is still small and if he has entered puberty, the child may choose to live with the father or mother, this depends on the wishes of the child. However, if a child who has entered puberty chooses to live with his mother, the mother may not restrain the child from being with his father and vice versa. This is done to meet the needs of love and attention from both parents which are still very much needed by puberty children.